(untitled) (Research, Society and Development, 2020)
The objective of this study was to determine the influence of larval feeding of queens of Africanized bees (Apis mellifera L.) on the acceptance of transferred larvae, during the time of development until adulthood, as well as the influence of different forms of larval feeding on body mass. right after the emergency. For the production of queens, the Doolitle method was used, in which different amounts of royal jelly were introduced, according to the treatments below. TR (20): transfer of the larva in 20μl; TR (170): Transfer of the larva in 170μl and TR (20 + 150): Transfer of the larva in 20μl with supplementation of 150μl in 72 hours after transfer. The acceptance of the larvae was similar in all treatments, but the practice of reapplying food in the domes 72 hours after the larval transfer caused mortality in the larvae. The growth time of the larvae was different among all treatments (p <0.05), where the TR (170) showed a faster development. When assessing the body mass of queens when they emerged, it was noticed that TR (20) and TR (170) did not differ from each other (p> 0.05), but both were superior to TR (20 + 150) (p <0, 05). It was concluded that transferring larvae in large quantities of royal jelly for the production of queens does not influence the acceptance of the transferred larvae, but on the time of larval development. However, the influence on growth time is almost inexpressive and the supply of food in a second moment for the same larva is not recommended.